Superamphiphilic carbon from sawdust activated by oxygen/argon mixtures promoting the oxidation of benzyl alcohol in Pickering emulsion. Issue 17 (9th August 2021) - Fan, Honglei; Chen, Bingfeng; Chen, Chunjun; Zhang, Zhaofu; Song, Jinliang; Yang, Guanying; Han, Buxing
Abstract : Superamphiphilic carbon from sawdust activated by oxygen/argon mixtures enhanced the efficiency of selective oxidation of benzyl alcohol by enriching the reactants around catalysts and inducing the formation of Pickering emulsions. Abstract : Superamphiphilic carbon from sawdust was directly prepared in oxygen/argon. The C element is responsible for the hydrophobic nature and the O element in anhydride and carboxyl groups endows carbon with hydrophilicity. Furthermore, in the oxidation of benzyl alcohol, conversion and yield could reach 94% doubled those of blank experiments in Pickering emulsion due to superamphiphilicity of carbon.